Benefits, Facilitators, and Recommendations for Digital Health Academic-Industry Collaboration: A Mini Review - Ford, Kelsey L.; Portz, Jennifer D.; Zhou, Shuo; Gornail, Starlynne; Moore, Susan L.; Zhang, Xuhong; Bull, Sheana (Frontiers in Digital Health, 2021)
Digital health remains a growing and challenging niche in public health practice. Academic-industry collaboration (AIC) offers a mechanism to bring disparate sectors together to alleviate digital health challenges of engagement, reach, sustainability, dissemination, evaluation, and equity. Despite the ongoing endorsements for AIC in digital health, limited understanding exists of successful AIC exists. Most published research highlights the barriers of collaboration rather than efficacy, leaving collaborators asking: what are the benefits and facilitators of AIC and do they apply in digital health? As an initial effort to fill the gap in the literature, the purpose of this mini review outlines the benefits and facilitators from previous AIC and offers recommendations specific to digital health.